A study of network-building HR practices for TMT, strategic flexibility and firm performance: The moderating role of environmental uncertainty. Issue 1 (25th February 2014) - Lin, Yaqing; Zhao, Shuming; Li, Na
Abstract : Purpose: – The purpose of this study is to introduce strategic flexibility as an important dynamic capability into the field of strategic human resource management (SHRM) and explore its mediating role between network-building HR practices for top management team (TMT) and firm performance. Moreover, based on the context of transition economy in China, the authors examine environmental uncertainty as a moderator in these relationships and empirically test the questions above. Design/methodology/approach: – The authors have conducted questionnaire surveys on 780 top managers in 390 companies mainly located in Beijing, Tianjin, Shanghai, Jiangsu and Zhejiang and finally received 241 valid samples. Findings: – The results show that network-building HR practices have positive effects on firm performance and strategic flexibility plays a fully mediating role between them. In addition, environmental uncertainty moderates the relationship between network-building HR practices for TMT and strategic flexibility, while it has no moderating effect in the relationship between strategic flexibility and firm performance. Originality/value: – These conclusions have important implications for the development and application of SHRM in dynamic environments. Theoretically, the authors enrich the functions of network-building HR practices for TMT and provide the evidence to advocate the development of the innovative HR practices in China. In terms of the practical implications of the study, it is argued that network-building HR practices for TMT and strategic flexibility can help firms to deal with uncertainty and achieve high performance, which provides constructive guidance in the development of enterprises in the China's transition economy.